Implementasi Akuisisi Data Biosignal Manusia dengan Mekanisme Store-Forward Pada Perangkat Smartwatch Berbasis Wear Os Menggunakan Protokol Komunikasi Bluetooth Low Energy - Apriyanto J.P.L Tobing; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The most important thing from IoT Smart Healthcare in measuring a patient's health condition is the ability to acquire the patient's biosignal data. Wearable smartwatch devices can be used to acquire biosignal data in the form of heartbeats and data in the form of the number of footsteps to acceleration. However, data acquisition cannot be done for a long time due to the computational and resource limitations of the device. A strategy is needed in acquiring data so that data acquisition is still be done optimally. The proposed strategy for resolving these problems consists of applying the indirect model and the store-forward method. In the indirect model, a gateway is developed on a smartphone device and uses the BLE and MQTT communication protocols. The store-forward method is applied to smartwatch devices so that data acquisition continues even though it cannot connect directly to the gateway device. This research successfully implemented the proposed system. The test results provide a ratio of the success of sending data from sensor nodes to the cloud of 0.998. This success value is influenced by the MQTT protocol, because the success value of sending data using the BLE communication model of 1 for each test scenario. Projected increase in memory every 15 minutes when acquiring data using the store-forward method of 100 KB and data entry of 2,340. There are differences in the delay in each communication protocol. In communication with BLE, the delay during the sending process varies but is stable with an average of 1.13 seconds.